Stress and distortion measurements in a 45 degree swept box beam subjected to bending and to torsion - Zender, George W. (National Advisory Committee for Aeronautics, 1948)
An untapered aluminum-alloy box beam, representing the main structural component of a full-span, two-spar, 45 degree swept wing with a carry-through bay, was subjected to tip bending and twisting loads and its stresses and distortions were meaured. Only symmetrical loading was considered and the stresses were kept below the proportional limit.
NACA TN No. 1525.